2018
DOI: 10.3389/fnbeh.2018.00177
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment During Adolescence Acts as a Protective and Therapeutic Tool for Ethanol Binge-Drinking, Anxiety-Like, Novelty Seeking and Compulsive-Like Behaviors in C57BL/6J Mice During Adulthood

Abstract: Repetitive drug/ethanol (EtOH) binge-like consumption during pre-addictive stages favors a transition to addiction in vulnerable organisms. Experimental evidence points to the therapeutic and preventive effects of environmental enrichment (EE) on drug and EtOH addiction; however, little is known regarding EE modulation of binge-like consumption in non-dependent organisms. Here, we explore the impact of early EE on binge-like EtOH consumption: (1) we test whether early EE exposure prevents binge-like EtOH intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 73 publications
(146 reference statements)
3
16
0
Order By: Relevance
“…Preclinical research have demonstrated that environmental enrichment (EE), where animals are socially grouped and exposed to sensorial and motor enriched housing conditions (Crofton et al, 2015 ), prevents and also modulates ongoing EtOH intake and drug addiction as well (Nithianantharajah and Hannan, 2006 ). Consistent with this work, we have recently extended this knowledge by showing the therapeutic and protective role of EE on excessive binge-like consumption of EtOH (Rodríguez-Ortega et al, 2018 ). Interestingly, there is experimental evidence indicating that EE exposure also reduces anxiety (Peña et al, 2006 , 2009 ; Sztainberg et al, 2010 ; Rodríguez-Ortega et al, 2018 ), compulsivity (Muehlmann et al, 2012 ; Bechard et al, 2016 ; Rodríguez-Ortega et al, 2018 ) and modulates EtOH (Deehan et al, 2007 , 2011 ; de Carvalho et al, 2010 ; Rodríguez-Ortega et al, 2018 ) and sucrose intake (Brenes and Fornaguera, 2008 ; Grimm et al, 2010 , 2013 , 2016 ).…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…Preclinical research have demonstrated that environmental enrichment (EE), where animals are socially grouped and exposed to sensorial and motor enriched housing conditions (Crofton et al, 2015 ), prevents and also modulates ongoing EtOH intake and drug addiction as well (Nithianantharajah and Hannan, 2006 ). Consistent with this work, we have recently extended this knowledge by showing the therapeutic and protective role of EE on excessive binge-like consumption of EtOH (Rodríguez-Ortega et al, 2018 ). Interestingly, there is experimental evidence indicating that EE exposure also reduces anxiety (Peña et al, 2006 , 2009 ; Sztainberg et al, 2010 ; Rodríguez-Ortega et al, 2018 ), compulsivity (Muehlmann et al, 2012 ; Bechard et al, 2016 ; Rodríguez-Ortega et al, 2018 ) and modulates EtOH (Deehan et al, 2007 , 2011 ; de Carvalho et al, 2010 ; Rodríguez-Ortega et al, 2018 ) and sucrose intake (Brenes and Fornaguera, 2008 ; Grimm et al, 2010 , 2013 , 2016 ).…”
Section: Introductionsupporting
confidence: 78%
“…Consistent with this work, we have recently extended this knowledge by showing the therapeutic and protective role of EE on excessive binge-like consumption of EtOH (Rodríguez-Ortega et al, 2018 ). Interestingly, there is experimental evidence indicating that EE exposure also reduces anxiety (Peña et al, 2006 , 2009 ; Sztainberg et al, 2010 ; Rodríguez-Ortega et al, 2018 ), compulsivity (Muehlmann et al, 2012 ; Bechard et al, 2016 ; Rodríguez-Ortega et al, 2018 ) and modulates EtOH (Deehan et al, 2007 , 2011 ; de Carvalho et al, 2010 ; Rodríguez-Ortega et al, 2018 ) and sucrose intake (Brenes and Fornaguera, 2008 ; Grimm et al, 2010 , 2013 , 2016 ). Elevated anxiety (Wand, 2005 ), high sensitivity to stress (Goeders, 2003 ) and/or high compulsivity (Figee et al, 2016 ) might significantly increase vulnerability to develop addiction; on the other hand, we have reported that EE modulate spontaneous binge-intake.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations